Computational Methods in Transport: Verification and Validation - Graziani, Frank.; Graziani, Frank. (Lecture Notes in Computational Science and Engineering, 2008)
The focus of this book deals with a cross cutting issue affecting all particle transport algorithms and applications; verification and validation (V&V). In other words, are the equations being solved correctly and are the correct equations being solved? Verification and validation assures a scientist, engineer or mathematician that a simulation code is a mirror of reality and not just an expensive computer game. In this book, we will learn what the astrophysicist, atmospheric scientist, mathematician or nuclear engineer do to assess the accuracy of their code. What convergence studies, what error analysis, what problems do each field use to benchmark and ascertain the accuracy of their transport simulations. Is there a need for new benchmark problems? Are there experiments that can be used to help validate the simulation results? If not, are there new experiments that could address these issues? These are all questions raised in this proceedings of the Second Computational Methods in Transport Workshop.